Emergency contraceptive pill use among women of reproductive age in Pathein, Myanmar - Khin Wai Wai Htun; Korravarn Yodmai; Pimsurang Taechaboonsermsak (College of Public Health Sciences, Chulalongkorn University, 2019)
Purpose - Emergency contraceptive pills (ECPs) allow a second chance to prevent unwanted pregnancy in unplanned sexual intercourse. Therefore, it helps reduce the rate of induced or unsafe abortions. Although they are available over-the-counter in Myanmar, relevant information remains improperly known by women and its use is limited. The purpose of this paper is to identify the prevalence and associated factors of ECPs use among women of reproductive age in the delta region of Myanmar. Design/methodology/approach - This community based cross-sectional study was conducted in Pathein Township, Ayeyarwady Division, Myanmar from March 30 to April 29, 2018. This study was conducted among 238 respondents selected using multistage sampling and face-to-face interviews employed structured questionnaires. Multiple logistic regression was used to analyze the associations among variables. Findings - The prevalence of ECPs use among reproductive aged women was 11.3 percent. Factors significantly associated with ECPs use were high monthly family income (AOR=4.50, 95% CI=1.31-15.48), condom use (AOR=4.40, 95% CI=1.07-18.16) and never having experienced pregnancy (AOR=6.20, 95% CI=2.06-18.67). Originality/value - To improve the use of ECPs, extension of services such as opening hours or working days is needed. The government and NGOs should implement the services to support women who have encountered unplanned sexual intercourse so that unwanted pregnancy can be prevented.